Reactions under increased pressure: The reactivity of functionally substituted 3-oxo-2-arylhydrazones toward active methylene reagents in Q-tube - AlMarzouq, Douaa Salman (European Journal of Chemistry, 2021)
A one-pot two-component reaction of 3-oxo-2-arylhydrazones with active methylene nitriles under high pressure in a Q-tube safe reactor was reported. Comparison between conventional and Q-tube safe reactor-assisted synthesis of organic compounds was done by comparing total reaction time and percentage yield. The results show that the compound 5-cyano-6-oxo-1,4-diphenyl-1,6-dihydro-pyridazine-3-carboxylic acid ethyl ester (3) was synthesized within 2 h in a yield of 97%. In addition, the pyrazolo[3,4-c]pyridines 5b and 5c were obtained in yields of 93 and 95% within 1 h reaction time, respectively. The obtained results suggest that Q-tube safe reactor-assisted syntheses were led to higher product yields within very short reaction times.